Relationship between Physicochemical and Habitat Parameters with Abundance of Benthic Macroinvertebrates in Assessment of Water Quality - Farzad Mehrjo; Seyed Hossein Hashemi; Asghar Abdoli (Sustainable Earth Trends, 2024)
Benthic macroinvertebrates are commonly used for assessment of water quality. Usually, these insects in rivers are present, easily collected, not moving much and it is easy to detect kinship. Benthic macroinvertebrates can also show changes in water quality and as sensitive indicators of environmental change are used. Jajrud River originated from the Elburz Mountains in northern Tehran. A sampling of Jajrud River benthic macroinvertebrate organisms from a Surber sampler device with an area of 900 cm2 and mesh size of 250-micron was repeated three times at each station. Physicochemical parameters including Elevation, Depth, Flow Velocity (WatFlow), Water Temperature (WatTem), Turbidity, Total Suspended Solids (TSS), Electrical conductivity (EC), Fecal Coliform, Phosphate, Nitrate, Nitrite, Ammonium, Dissolved oxygen (DO), pH, Chemical Oxygen Demand (COD) Biochemical Oxygen Demand (BOD) were measured. Habitat parameters such as Epifaunal Substrate (EFAC), Embeddedness (Embed), Velocity and Depth Regimes (Vel), sediment deposition (Sedimen), Channel Flow Status (Channelf), Channel Alteration (Channelt), Frequency of Riffles (Freq), Bank Stability (Bankstu), Vegetative Protection (Veg) and Riparian Vegetative Zone Width (RipaVeg) were reviewed. Then according to bioassessment protocols and ratings based on a zero to 20, for relationship between physicochemical and habitat parameters with an abundance of benthos grouping and assessment of water quality, from CANOCO software and principal component analysis (PCA) was used. The results showed that the water quality in the downstream Jajrud is unfavorable and appropriate management measures should be taken to improve the river's water quality.